France : Financial Sector Assessment Program-Detailed Assessment of Observance of Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses key findings of the Detailed Assessment of Observance of Insurance Core Principles for France. The assessment reveals that insurance regulation and supervision are still predominantly carried out using a Solvency I approach. The insurance sector remained resilient through the recent global financial crisis. A thorough approach to assessing insurer technical provisions and their coverage by admissible assets has led to financially sound insurers. Individual French insurance companies have not needed any government or industry support.